(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article is about the importance of learning English Language. English as a language has great reach and influence. it is taught all over the world. It is also stressed that, English is the language of international communication for all mankind. The value of English in today`s world cannot be overestimated. Nowadays more than 1 billion people speak in this language. English is also the language of business. After all it is necessary to reckon with the choice of more than 1 billion people who speak it. And if a half of them are native speakers, about 600 million choose it as foreign. English is the dominant business language and it has become almost a necessity for people to speak English if they are to enter a global workforce, research from all over the world shows that cross-border business communication is most often conducted in English. Its importance in the global market place therefore cannot be understated, learning English really can change your life.